Demographic Change beyond the Urban-Rural Divide: Re-Framing Spatial Differentiation in the Context of Migration Flows and Social Networks - Huning, Sandra; Bens, Oliver; Hüttl, Reinhard F. (DIE ERDE – Journal of the Geographical Society of Berlin, 2012)
Spatial differentiation can be analysed as both state of the art and as process. One important distinction in the analysis of spatial differentiation has been that between the urban and the rural. But the interrelationship of the urban-rural divide with other dimensions of spatial differentiation, such as demographic change, is increasingly unclear. Modern assumptions that urban areas are growth engines and rural areas lag behind have been replaced by the acknowledgement of much more heterogeneous development patterns. Neither extent nor direction of demographic change can be directly linked to a region’s classification as rural or urban today. The paper focuses on the question of how research on human flows and networks may contribute to such a framework and aims to draw attention to the coexistence of different kinds of flows and networks which interfere with each other, resulting in regionally specific spatial patterns and development paths. The paper suggests an extension of the analysis of cores and peripheries beyond the focus on key economic sectors, such as financial services, and taking into account individual and social networks of private households, migrants and commuters. Instead of understanding regional demographic change as the result of rational migratory decisions, due to regional push and pull factors, we aim to conceptualise it as related to the existence of social – multi-local, sometimes even transnational – networks that contextualise migration strategies of individuals or households. Consequently, we argue that such an analysis may help in obtaining a more detailed picture of demographic change as a mosaic of interrelated processes and raise awareness towards drivers of spatial differentiation beyond the urban-rural divide that may deserve more attention in the future.